1999
DOI: 10.1103/physrevlett.82.3078
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Geometry of Rocks

Abstract: The analysis of small-and ultra-small-angle neutron scattering data for sedimentary rocks shows that the pore-rock fabric interface is a surface fractal ͑D s 2.82͒ over 3 orders of magnitude of the length scale and 10 orders of magnitude in intensity. The fractal dimension and scatterer size obtained from scanning electron microscopy image processing are consistent with neutron scattering data.[S0031-9007(99)08945-0] PACS numbers: 61.43.Hv, 61.12.Ex, Owing to the limited size range over which the fractal prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 22 publications
7
102
0
Order By: Relevance
“…Moreover, the apparently universal surface fractal dimension of ballisticlike deposits is another important point for further investigation and suggests possible applications of this class of growth model. Indeed, the estimate D F = 2.9 is very close to the value D F ≈ 2.85 obtained experimentally in sandstones [38,39], and not very far from D F = 2.7 − 2.8 obtained in gold vapor deposition [40]. Another interesting question is what happens in ballisticlike models with varying angles of deposition, which have been recently applied to growth of silicon or silicon compounds [41,42,43].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the apparently universal surface fractal dimension of ballisticlike deposits is another important point for further investigation and suggests possible applications of this class of growth model. Indeed, the estimate D F = 2.9 is very close to the value D F ≈ 2.85 obtained experimentally in sandstones [38,39], and not very far from D F = 2.7 − 2.8 obtained in gold vapor deposition [40]. Another interesting question is what happens in ballisticlike models with varying angles of deposition, which have been recently applied to growth of silicon or silicon compounds [41,42,43].…”
Section: Discussionmentioning
confidence: 80%
“…Experimental observations, however, indicate that pore roughness may exhibit self-similar characteristics over a wide range of length scales. Experimental studies based on different experimental techniques [23][24][25] (e.g., scanning electron microscopy, small-angle neutron scattering, nitrogen adsorption isotherm) have demonstrated that, for instance, the pore space of sandstones and shales is approximately fractal over length scales ranging from 10Å to 100 µm, with corresponding fractal dimensions varying between 2.57 and 2.87. Other experimental studies 26,27 have proven that fractured-rock wall surfaces also display fractal and multifractal properties over a range of scales between 0.1 µm to 1 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The pore becomes less disperse, and the separation gets better as the data points move closer to the center of mean value. The rule has not been reported before (Angulo et al 1992;Shen et al 1995Shen et al , 1998Becker et al 1997;Perez and Chopra 1997;He and Hua 1998;Radlinski et al 1999;Perez and Miguel 2001;Libny et al 2001;Bijan 2003;Li 2004;Ma et al 2005;Han et al 2006;Li and Horne 2006;Sondergeld et al 2010;Sigal 2013).…”
Section: Fractal Model Of Microheterogeneitymentioning
confidence: 80%
“…After long-term water flooding in heavy oil reservoir, fractal dimensions of both large and small pores, variable coefficient, skewness, and characteristic function of pore structure decrease as the water cut increases. It indicates that the microheterogeneity of core decreases after long-term water flooding (Angulo et al 1992;Shen et al 1995Shen et al , 1998Becker et al 1997;Perez and Chopra 1997;He and Hua 1998;Radlinski et al 1999 Quantitative study on variation of microheterogeneity with 3D pore network model 3D pore network model is an important tool to study micropore structure and macroscopic seepage characteristics of reservoir. The network model is composed of throats and connected pore bodies.…”
Section: Fractal Model Of Microheterogeneitymentioning
confidence: 99%
See 1 more Smart Citation